The historical memory of Central America’s Independence, narratives in the context of the Bicentennial’s commemoration - Rodríguez Vargas, María José (2022)
The article describes the historical narratives of the Central American Independence, in the context of the Bicentennial’s commemoration, presented by senior students who are part of the Costa Rican scholar system, specifically to the Redentorista San Alfonso High School, located in Alajuela City’s urban zone, Costa Rica. The main objective is to recognize the historical memory of a students’ group that are concluding their secondary education. To achieve this goal, it has been made a study case with four students, through a workshop developed with three pedagogical moments. The results allow to reconstruct and recognize the historical narratives of these students and identify their historical consciousness of the Central America’s Independence.